The Practice of Identity Politics in North Sumatra: Analysis of Siyasah and Islamic Law - Harahap, Hikmatiar; ansari, ansari; khoiri, Nispul (Faculty of Law, Universitas Pekalongan, 2024)
Abstract The background to the problem in this dissertation is related to the practice of identity politics in the 2018 North Sumatra Governor Election with an objective study. The practice of identity politics that can be traced is related to the use of religious and tribal (regional) identities. The 2018 North Sumatra Governor election was attended by two couples, namely Eramas and Djoss. The Eramas couple is Muslim-Muslim while Djoss is Muslim-Christian, as well as in tribal (regional) identity the Eramas couple is identified as a native son while Djoss is perceived as an immigrant even though Sihor Sitorus is from the Batak tribe. Thus, the practice of identity politics in the 2018 North Sumatra Governor Election was analyzed based on the study and approach of Siyasah and Islamic Law. The aim is to find out the background to the emergence of identity politics as well as the views and analysis of Siyasah, Islamic Law, and political parties regarding identity politics. The results of this research are, firstly, the concept of Siyasah can be maximized by Siyasah playing an active role through ta'aruf so that it can minimize the practice of identity politics because ta'aruf leads to understanding and understanding the interests of society while the benefit in the form of the psychological power of goodness is responsibility in the form of unity and eternal and complete unity. Meanwhile, the Islamic Law aspect, emphasizes the ethical-legal concept in the form of the emergence of awareness by all elites and the interest in existing rules that must be obeyed and implemented. Meanwhile, in the political party aspect, more emphasis is placed on cadre education by each party to create militant and enthusiastic cadres. In Siyasah's view, identity politics is a product of siyasah wadh'iyyah which shows failure in carrying out amar ma'ruf or evil in terms of social control in the nation and state.